Institutions and Innovations as Sources of Productivity Growth Cross-Country Evidence - Thomas Strobel (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2010)
The investigation of the determinants of economic growth plays an important role forour understanding of the sources of cross-country income differences. This paper analyzesthe effects of institutions and innovations on country productivity growth. The empiricalevidence shows that institutions and innovations matter, in particular for human capitalefficiency. Without controlling for endogeneity the effect of innovations turns significantonly when aggregate institutions indexes or human capital efficiency are included.When controlling for endogeneity innovations become insignificant, but more institutionalvariables become relevant. Under robustness checks innovations indeed have a directeffect on country productivity growth moderated by a countrys human capital efficiency.Allowing for three alternative institutional variables does not change the effects of theinstitutional variables of interest.
Keywords: O30; O43; O50; 330; Productivity growth; institutions; information and communication technology; research and development; panel regressions; Produktivität; Wirtschaftswachstum; Innovation; Institutionalismus; Vergleich; OECD-Staaten